EVALUASI PENERAPAN SANITASI DI TEMPAT AGROWISATA NANAS TANGKIT BARU, SUNGAI GELAM, KABUPATEN MUARO JAMBI, JAMBI TAHUN 2023 - Fitri, Rahmi yulia; Sanjaya, Sindu; Mallini, Hemalia; Rodhiyah, Zuli (Lingkar: Journal of Environmental Engineering, 2023)
Tangkit Pineapple Agrotourism Area is the center of pineapple fruit production centers in Jambi Province and is the largest pineapple fruit agrotourism site in Jambi. As a tourist spot for pineapple fruit production centers in Jambi, the safety and comfort of visitors must be maintained to avoid the threat of various diseases through the provision of good sanitation facilities. The study aims to determine the description of Tangkit Pineapple Agrotourism sanitation. The study used a qualitative descriptive method, using a public places sanitation inspection instrument. The variables observed were the tourist environment including clean water, public toilets, waste water disposal, waste management, counseling facilities, health facilities and fire extinguishers. Data collection used observation sheets by means of transects throughout the Tangkit Pineapple Agrotourism area. The results of observations were compared with the standards of sanitation facilities and infrastructure, and presented in descriptive form. In general, the sanitation condition of the Tangkit Pineapple Agrotourism area still does not meet the applicable requirements. Liquid and solid waste management has not been done properly. Meanwhile, health facilities and fire extinguishers as supporting facilities are also not found. These results indicate the high risk of health and safety of visitors. Keywords: Evaluation, Sanitation, Public Places, Agrotourism.